The predictive value of oxidative stress index in patients with confirmed SARS-COV-2 infection - Osredkar, Joško (Acta chimica slovenica, 2022)
Disbalance balance between oxidants and antioxidants is called oxidative stress and could be presented as oxidative stress index (OSI). OSI is determined by the reactive oxygen metabolites (d-ROM test) to assess oxidants and the plasma antioxidant capacity test (PAT test) to measure antioxidants. The aim of the study was to evaluate the predictive value of OSI in the disease COVID-19. d-ROMs results were the highest in the SARS-CoV-2 POSITIVE group (365+/-112), lower in the SARS-CoV-2 NEGATIVE group (314+/-72.4), and the lowest in an INTENSIVE CARE UNIT group (ICU) (277+/-142) U.Carr. PAT test values were the lowest in the SARS-CoV-2 POSITIVE group (2762+/-387), higher in the ICU group (2772 +/-786), and the highest in the SARS-CoV-2 NEGATIVE group (2808+/-470), and are not statistically significantly different (P>0.05), while OSI was: healthy with average value of 49 and the critical ill with average value of 109 (P = 0.016). Cut-offs for predicting ICUs admission was at OSI 62, with 80.0% sensitivity and 68.2% specificity.
Keywords: Oksidativni stres; OSI Index; Oxidative stress; SARS-CoV-2